2019
DOI: 10.1101/801845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A fully automated deep learning pipeline for high-throughput colony segmentation and classification

Abstract: Background: Adenine auxotrophy is a commonly used non-selective genetic marker in yeast research.It allows investigators to easily visualize and quantify various genetic and epigenetic events by simply reading out colony color. However, manual counting of large numbers of colonies is extremely timeconsuming, difficult to reproduce and possibly inaccurate.Results: Using cutting-edge neural networks, we have developed a fully automated pipeline for colony segmentation and classification, which speeds up white/re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It is also possible to treat cells directly with tetrazolium to induce a rapid transition from white to red, specifically in Grande cells (Hess et al, 2009). While the pipeline in (Carl et al, 2020) performs admirably, and could be modified for Petite detection with the red/white colony assay, there are two disadvantages to using the red/white assay over our experimental approach. First, the red/white assay requires experimental constraints on media (adenine limited media) and the genetic background of the strains, whereas large/small colony detection only requires constraints on the media.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible to treat cells directly with tetrazolium to induce a rapid transition from white to red, specifically in Grande cells (Hess et al, 2009). While the pipeline in (Carl et al, 2020) performs admirably, and could be modified for Petite detection with the red/white colony assay, there are two disadvantages to using the red/white assay over our experimental approach. First, the red/white assay requires experimental constraints on media (adenine limited media) and the genetic background of the strains, whereas large/small colony detection only requires constraints on the media.…”
Section: Discussionmentioning
confidence: 99%
“…Second, for red pigments to form, experimentalists often need to wait further after colony growth or apply chemical treatments which decrease experimental efficiency compared to our approach. With respect to the object detection pipeline in (Carl et al, 2020), one downside is that it requires post-processing of segmentation results, including heuristics on eccentricity and absolute size of colonies in pixels. Furthermore, assuming perfect segmentation in the study by Carl et al (where segmentation accuracy is not reported), petiteFinder still achieves higher accuracy in Grande/Petite classification compared to white/red classification in experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, if components of the adenine synthesis pathway are expressed at low level (pink phenotype), classification can vary between researchers and screens, potentially leading to erroneous and not fully reproducible results. To reduce these issues, we have developed a highly accurate and automated colony classification method based on neuronal networks with whole plate images as input (Carl et al;bioRxiv, doi: https://doi.org/10.1101/801845). In this protocol we describe in detail the procedures for plating and imaging as used for the pipeline training, which are crucial to achieve optimal results.…”
Section: Introductionmentioning
confidence: 99%